2021
DOI: 10.3390/pathogens10060693
|View full text |Cite
|
Sign up to set email alerts
|

The Usefulness of a Duplex RT-qPCR during the Recent Yellow Fever Brazilian Epidemic: Surveillance of Vaccine Adverse Events, Epizootics and Vectors

Abstract: From 2016 to 2018, Brazil faced the biggest yellow fever (YF) outbreak in the last 80 years, representing a risk of YF reurbanization, especially in megacities. Along with this challenge, the mass administration of the fractionated YF vaccine dose in a naïve population brought another concern: the possibility to increase YF adverse events associated with viscerotropic (YEL-AVD) or neurological disease (YEL-AND). For this reason, we developed a quantitative real time RT-PCR (RT-qPCR) assay based on a duplex Taq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 59 publications
(83 reference statements)
1
1
0
Order By: Relevance
“…The YFV molecular sequence obtained was closer to West African sequences ( Fig. 5 ), than to American sequences previously reported [ 42 ]. This phenomenon could be associated with the continuous introduction of African YFV into the America [ 43 ].…”
Section: Discussionsupporting
confidence: 63%
“…The YFV molecular sequence obtained was closer to West African sequences ( Fig. 5 ), than to American sequences previously reported [ 42 ]. This phenomenon could be associated with the continuous introduction of African YFV into the America [ 43 ].…”
Section: Discussionsupporting
confidence: 63%
“…Data regarding PCR sensitivities are scarce. A Brazilian study conducted after the last outbreak from 2016 to 2018 indicated detection rates of 8.9% in serum and 50% in blood samples during the viremic phase [98]. Urine sample sensitivity was evaluated as 25% [99].…”
Section: Diagnosismentioning
confidence: 99%